Modelo multicritério para definição de ações de educação ambiental na gestão de resíduos sólidos domiciliares - FRAMESCHE, LETICIA (2022)
Due to the diversity and excessive generation of Urban Solid Waste (USW), its adequate management has become one of the most complex challenges faced by public managers and decision makers, given the negative impacts they cause, especially in developing countries, where the scarcity of financial, technical, professional and structural resources make it impossible to adopt sustainable waste management structures. Thus, the proposition of methods, tools, instruments, and legislations that are feasible for replication, as well as the help of stakeholders for fundamentals, are necessary and relevant to mitigate the challenges of this scenario. Therefore, the objective of this study was to systematize, apply and evaluate a model, which allows municipal decision makers to order Environmental Education (EE) actions based on criteria and sub-criteria for the improvement of the adequate management of Household Solid Waste (HSW). For this, two rounds of the Electronic Delphi method (23 experts, distributed by the regions of Brazil) to evaluate AE actions and subcriteria, from the literature, were used, resulting in five AE actions and 14 subcriteria, of common consensus (≥65%). Such results were the basis for structuring the hybrid model constituted by the Analytic Hierarchy Process (AHP), for assigning weights to criteria and subcriteria, and the Preference Ranking Organization METHod for Enrichment Evaluation (PROMETHEE), for ranking AE actions. Subsequently, the model was replicated and evaluated in three case studies, by municipal stakeholders, based on local characteristics and needs. The rankings identified the EE action "regular and long-term campaigns" as the most significant and prioritized for decision-making in just over 33% of the scenarios, and in approximately 67% as the second most appropriate, however, "lectures/seminars" as the least appropriate, close to 67%. As for the evaluation of the model, it was considered an adequate, replicable, useful and strategic tool. Therefore, the study fills gaps and offers theoretical, practical and political implications, serving as a stimulus for the development of public policies with a multidisciplinary approach, and thus, encouraging the achievement of the eleventh and twelfth sustainable development goals, related to HSW.